Prospect and Problems of Tourism Development in Nepal : A Case Study on Bhaktapur Darbar Square - Dahal, Ananta Raj (Historical Journal, 2020)
Tourism sector is a very importance in Nepalese’s economic activities. In this sector there are so many problems and opportunity. In this research had analysed the problems and prospects of tourism development in Nepal with reference to Bhaktpur Durbar Square (BDS) in Bhaktpur district. Primary data were used for the main information and secondary data also used for supplementary sources of information. Primary data collected by direct personal interview through semi-structural questioner. Both local trade/business people and tourist those who were available in the time of survey were used as a samples. Tourist visit here for holiday pleasure, business and research purpose. Length of tourist stay is very few and time of re visit also few. For the development of tourism sector Nepal increase physical facilities and improve infrastructure of old and new tourism destination.